Study of the yeast cytosolic Hsp70-system in protein homeostasis and life span regulation - Western blots of SDS-PAGE gels with primary antibodies against Hsp70p and Pgk1p - Andersson, Rebecca; Nyström, Thomas (University of Gothenburg, 2020)
Our study aims to answer the question "Which functions of the Hsp70 class of molecular chaperones are essential for yeast to maintain a standard replicative life span?". To answer this question, we utilised the disparate functions of the Hsp70's Ssa1 and 2 and their paralog Ssa4 in a yeast strain that lacks Ssa1/2 but has an ectopically increased production of Ssa4. We have gathered data on the behaviour of several different markers for protein aggregation under different circumstances, as well as data on proteins from other classes of molecular chaperones. The bulk of the data is in the form of multichannel microscopy images from widefield microscopy, with a few sets of western blots of protein extracts.

WT ssa12DD and ssa12DDSSA4OE: Western blots of SDS-PAGE gels with protein extracts from yeast in mid-exponential growth. The yeast was grown in complete synthetic media with 2 % glucose as carbon source.
WT ssa12DD w chimaera plasmids: Western blots of SDS-PAGE gels with protein extracts from yeast in mid-exponential growth before and after 30 minutes of heat shock. The yeast was grown in complete synthetic media lacking leucine with 2 % glucose as carbon source.
The images are scans of western blot PVDF-membranes.
The image files are provided in TIFF format.

Vi har systematiskt studerat vilka funktioner hos de cytosoliska molekylära chaperonerna av klassen Hsp70 hos jäst som krävs för att upprätthålla en normal livslängd.

WT ssa12DD and ssa12DDSSA4OE: Western blots av SDS-PAGE geler med proteinextrakt från jäst i mitten av den exponentiella tillväxtfasen. Jästen är odlad i komplett syntetiskt media med 2 % glukos som kolkälla.
WT ssa12DD w chimaera plasmids: Western blots av SDS-PAGE geler med proteinextrakt från jäst i mitten av den exponentiella tillväxtfasen före och efter 30 minuters värmestress. Jästen är odlad i komplett syntetiskt media utan leucin med 2 % glukos som kolkälla.
Bilderna är inskannade western blot PVDF-membran.
Bildfilerna är i TIFF-format.
Studier av det cytosoliska Hsp70-systemet från jäst och dess roll i proteinhomeostas och reglering av livslängd - Western blots av SDS-PAGE-geler med primära antikroppar mot Hsp70p och Pgk1p
Keywords: Molecular Chaperones; Molekylära chaperoner; HSP70 Heat-Shock Proteins; HSP70-värmechockproteiner; Proteostasis Deficiencies; Proteostasbrist; Cell Biology; Cellbiologi; Microbiology; Mikrobiologi; Cell and Molecular Biology; Cell- och molekylärbiologi; Molecular Biology; Molekylärbiologi